2021
DOI: 10.1038/s41598-021-91368-z
|View full text |Cite
|
Sign up to set email alerts
|

Aspartate aminotransferase to alanine aminotransferase ratio is associated with frailty and mortality in older patients with heart failure

Abstract: Frailty is a common comorbidity associated with adverse events in patients with heart failure, and early recognition is key to improving its management. We hypothesized that the AST to ALT ratio (AAR) could be a marker of frailty in patients with heart failure. Data from the FRAGILE-HF study were analyzed. A total of 1327 patients aged ≥ 65 years hospitalized with heart failure were categorized into three groups based on their AAR at discharge: low AAR (AAR < 1.16, n = 434); middle AAR (1.16 ≤ AAR < 1.70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
(30 reference statements)
0
18
0
Order By: Relevance
“…Besides high serum AST with normal ALT could reflect widespread skeletal muscle pathology (37). Thus, AST to ALT ratio may be a good indicator for frailty and sarcopenia in older patients (38) and multivariate logistic regression model also showed that fasting insulin (OR=0.919, [95%CI: 0.878-0.922] P=0.000) and AST to ALT ratio (OR=2.771, [95%CI: 1.544-2.342] P=0.000) were risk factors for sarcopenia. Although TP, ALB and PA can all reflect the nutritional status of the body, ALB and PA are more recommended in the evaluation of the nutritional status of patients with sarcopenia, and their corresponding AUC is 0.604 and 0.609, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Besides high serum AST with normal ALT could reflect widespread skeletal muscle pathology (37). Thus, AST to ALT ratio may be a good indicator for frailty and sarcopenia in older patients (38) and multivariate logistic regression model also showed that fasting insulin (OR=0.919, [95%CI: 0.878-0.922] P=0.000) and AST to ALT ratio (OR=2.771, [95%CI: 1.544-2.342] P=0.000) were risk factors for sarcopenia. Although TP, ALB and PA can all reflect the nutritional status of the body, ALB and PA are more recommended in the evaluation of the nutritional status of patients with sarcopenia, and their corresponding AUC is 0.604 and 0.609, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic venous congestion and hypoperfusion due to heart failure lead to liver dysfunction and abnormal liver function tests, with a subsequent increase in liver fibrosis markers. 2 So far, numerous liver fibrosis markers have been reported to be associated with poor prognosis in patients with heart failure [3][4][5] ; however, the optimal liver fibrosis marker for heart failure has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Maeda and his colleagues also revealed that AST/ALT is more strongly correlated with the 1-year mortality, independent of other covariates, other than ALT alone. This is likely because the AST and ALT proportion may offset the influence from liver dysfunction, thereby making AST/ALT more specific to muscle capacity [ 16 ]. ALT is a key enzyme in gluconeogenesis, whereby muscle protein is broken down to amino acids, which, in turn, converts alanine to alpha-ketoglutarate for glucose and/or energy production.…”
Section: Discussionmentioning
confidence: 99%